Advanced Practice Registered Nurses' Quality Improvement Efforts to Reduce Antipsychotic Use in Nursing Homes. Issue 1 (January 2019) - Flesner, Marcia; Lueckenotte, Annette; Vogelsmeier, Amy; Popejoy, Lori; Canada, Kelli; Minner, Donna; Galambos, Colleen; Rantz, Marilyn J.
Abstract : Supplemental Digital Content is Available in the Text.